AF ablation using a novel "single-shot" map-and-ablate spherical array pulsed field ablation catheter: 1-Year outcomes of the first-in-human PULSE-EU trial - Turagam, Mohit K; Neuzil, Petr; Petru, Jan; Funasako, Moritoshi; Koruth, Jacob S; Skoda, Jan; Kralovec, Stepan; Reddy, Vivek Y (Heart rhythm, 2024)
BACKGROUND: During pulsed field ablation (PFA), electrode-tissue proximity optimizes lesion quality. A novel "single-shot" map-and-ablate spherical multielectrode PFA array catheter that is able to verify electrode-tissue contact was recently studied in a first-in-human trial of atrial fibrillation (AF). OBJECTIVE: The aim of this study was to report lesion durability data, safety, and 12-month effectiveness outcomes. METHODS: The spherical PFA catheter, an all-in-one mapping and ablation system, was used to render anatomy and to deliver biphasic pulses (ungated 1.7 kV pulses; ∼40 seconds/application). Ablation sites included pulmonary veins (PVs) and, in selected patients, posterior wall and mitral isthmus. Follow-up was invasive remapping at ∼3 months, electrocardiograms, Holter monitoring at 6 and 12 months, and symptomatic and scheduled transtelephonic monitoring. The primary and secondary efficacy end points were acute PV isolation (PVI), PVI durability, and atrial arrhythmia recurrence. RESULTS: In the 48-patient AF cohort (paroxysmal, 48%; persistent, 52%), lesion sets included PVI (n = 48; 1.2 applications/PV), posterior wall (n = 20; 3.6 applications/posterior wall), and mitral isthmus (n = 11; 2.9 applications/mitral isthmus). Lesions were acutely successful for all 187 of 187 PVs (100%), 20 of 20 posterior walls (100%), and 10 of 11 mitral isthmuses (91%). Pulse delivery time, left atrial catheter dwell time, and procedure time were 61.5 ± 32.8 seconds, 53.9 ± 26.5 minutes, and 87.8 ± 29.8 minutes, respectively. Remapping (43/48 patients [89.5%]) revealed that 158 of 169 PVs (93.5%) were durably isolated. The only complication was a drug-responsive pericarditis. The 1-year Kaplan-Meier estimates of freedom from atrial arrhythmia were 84.2% (paroxysmal AF) and 80.0% (persistent AF). CONCLUSION: The single-shot spherical array PFA catheter can safely achieve durable lesions, translating into good clinical efficacy.
Keywords: senioři; Pulmonary Veins; Spherical array catheter; Pulsed field ablation; design vybavení; Pulmonary vein isolation; Time Factors; výsledek terapie; katetrizační ablace; Middle Aged; mužské pohlaví; recidiva; Equipment Design; Follow-Up Studies; Atrial fibrillation; Catheter ablation; následné studie; převodní systém srdeční; Catheter Ablation; ženské pohlaví; Humans; Recurrence; venae pulmonales; Heart Conduction System; fibrilace síní; časové faktory; lidé středního věku; elektrokardiografie ambulantní; Electrocardiography, Ambulatory; Female; Aged; Atrial Fibrillation; Treatment Outcome; lidé; Male